P2 Type Layered Solid-State Electrolyte Na2Zn2TeO6: Crystal Structure and Stacking Faults. Issue 15 (1st January 2019) - Li, Xinyu; Bianchini, Federico; Wind, Julia; Vajeeston, Ponniah; Wragg, David; Fjellvåg, Helmer
Abstract : The layered super-ionic conductor Na2 Zn2 TeO6 is a promising material for applications as electrolyte in solid-state batteries. Independent of synthesis route and conditions, a significant peak broadening of (1 0 1) is evident in collected X-ray diffraction data, which is not compatible with the standard structure model (space group P63 22 ). In this work, we describe sodium disorder and stacking faults in Na2 Zn2 TeO6 and identify the nature of the faults that are manifested by this peak broadening. First principle modeling was applied to describe the Na-distribution and support models on stacking faults. We describe the dominant fault as an in-plane shift causing local alignment of Te atoms along the layer stacking direction. This was experimentally verified by first constructing a supercell model of Na2 Zn2 TeO6 and simulating X-ray diffraction patterns for different densities of stacking faults, to help identifying a structural model that best matches experimental data. The Rietveld and in particular the stacking fault refinements, were found to perfectly describe the crystal structure and also the peak-broadening features. The stacking fault density in Na2 Zn2 TeO6 is ∼3%. This value appeared not to be susceptible to differences in synthesis conditions, including quenching and long-term annealing, as furthermore confirmed by in-situ X-ray diffraction data at temperatures between 25–600°C.